Impact of low health literacy on healthcare utilization in individuals with cardiovascular disease, chronic obstructive pulmonary disease, diabetes and mental disorders. A Danish population-based 4-year follow-up study - Friis, Karina (Eur J Public Health, 2020)
BACKGROUND: Previous research from the USA has shown that low health literacy is associated with higher hospitalization rates and higher rates of emergency service use. However, studies in a European context using more comprehensive health literacy definitions are lacking. The aim was to study the impact of low health literacy on healthcare utilization in a Danish context. METHODS: In this prospective cohort study, baseline survey data from 2013 were derived from a large Danish health and morbidity survey and merged with individual-level longitudinal register data for a 4-year follow-up period. The study included people in the general population (n = 29 473) and subgroups of people with four different chronic conditions: cardiovascular disease (CVD) (n = 2389), chronic obstructive pulmonary disease (COPD) (n = 1214), diabetes (n = 1685) and mental disorders (n = 1577). RESULTS: In the general population, low health literacy predicted slightly more visits to the general practitioner and admissions to hospital and longer hospitalization periods at 4 years of follow-up, whereas low health literacy did not predict planned outpatient visits or emergency room visits. In people with CVD, low health literacy predicted more days with emergency room visits. In people with mental disorders, difficulties in actively engaging with healthcare providers were associated with a higher number of hospital admission days. No significant association between health literacy and healthcare utilization was found for diabetes or COPD. CONCLUSIONS: Even though Denmark has a universal healthcare system the level of health literacy affects healthcare use in the general population and in people with CVD and mental disorders.